Species diversity of Odonata in Mt. Gutom Protected Landscape, Zamboanga del Norte, Philippines - JALILAH P. DICOL; EDDIE P. MONDEJAR; REAGAN JOSEPH T. VILLANUEVA (Society for Indonesian Biodiversity, 2024)
Abstract. Dicol JP, Mondejar EP, Villanueva RJT. 2024. Species diversity of Odonata in Mt. Gutom Protected Landscape, Zamboanga del Norte, Philippines. Biodiversitas 25: 4479-4486. Mount Gutom Protected Landscape is one of the remaining natural forests and one of the most important watersheds in the province of Zamboanga del Norte, Philippines. This study aimed to assess the species diversity and endemism of Odonata on Mt. Gutom. The field sampling was conducted on 7-20 December 2022. A combination of sweep netting and opportunistic sampling methods were used to collect samples. The five sampling sites were established in the forested and agricultural areas where water bodies and open areas are present. A total of 331 individuals belonging to 27 species of Odonata and representing 9 families and 18 genera were recorded at the five sampling sites. The endemism of Odonata was recorded at 59.26%, including two species under the near threatened category of the International Union for Conservation of Nature (IUCN). Also, the Philippine endemic Diplacina bolivari Selys, 1882 and Euphaea amphicyana Ris, 1930 were the most dominant and abundant dragonfly and damselfly species in three sampling sites, respectively. All sampling sites recorded moderate diversity, with a diversity index (H') value ranging from 1.724 to 2.694. Analysis of Similarity (ANOSIM) and dissimilarity between sampling sites showed that the highest average similarities were observed in the sampling sites located along the Sikitan River, agroecosystem, and Lower Gutom (67.41%), while sampling sites in Malikas and Upper Gutom had 90.59% dissimilarity. The results advocate the importance of protecting and conserving Mt. Gutom Protected Landscape to sustain the availability of resources required to support the different taxa present.